INTEGRITAS KEPEMIMPINAN DESA, UPAYA PENCEGAHAN KORUPSI PADA DANA DESA DI KABUPATEN BIREUN - Novita Sari; Muliawati Muliawati; Siti Hardiyanti; Nurul Fajri (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2023)
The research entitled Integrity of Village Leadership, Efforts to Prevent Corruption in Village Funds in Bireuen Regency, the researchers aimed to obtain information on the influence of the integrity of the leadership figure of the village head in Bireuen Regency to commit to not commit acts of corruption in managing village funds sourced from the APBN, and carried out by the leadership of the village head to prevent corruption in village funds that could harm state money. So far, there have been many cases of village leadership having integrity crises in managing state money, there are several village heads in Bireuen who have been ensnared in legal cases regarding the corruption of village funds. In this study, the researcher used a qualitative method in the form of a participant observation approach, where the researcher himself became the main instrument in collecting data in the field. The data collection techniques used are observation, interviews, documentation and literature study. The results showed that cases of corruption in village funds in Bireuen occurred, not because of a lack of supervision and law enforcement against village heads. Another factor that causes corruption in village funds is that they do not have strong personal integrity in village leadership. The integrity is in the form of honesty, keeping promises, loyalty, responsibility and fairness. There are two approaches to preventing village fund corruption in Bireuen, namely the psychological approach and local wisdom.